Tuberculosis Treatment Response Monitoring by the Phenotypic Characterization of MTB-Specific CD4+ T-Cells in Relation to HIV Infection Status - Nádia Sitoe; Mohamed I. M. Ahmed; Maria Enosse; Abhishek Bakuli; Raquel Matavele Chissumba; Kathrin Held; Michael Hoelscher; Pedroso Nhassengo; Celso Khosa; Andrea Rachow; Christof Geldmacher; on behalf of TB Sequel Consortium (Pathogens, 2022)
HIV infection causes systemic immune activation, impacts TB disease progression and hence may influence the diagnostic usability of Mycobacterium tuberculosis-specific T cell profiling. We investigated changes of activation and maturation markers on MTB-specific CD4+ T-cells after anti-tuberculosis treatment initiation in relation to HIV status and the severity of lung impairment. Thawed peripheral blood mononuclear cells from TB patients with (n = 27) and without HIV (n = 17) were analyzed using an intracellular IFN-γ assay and flow cytometry 2 and 6 months post-TB treatment initiation. H37Rv antigen was superior to the profile MTB-specific CD4+ T-cells phenotype when compared to PPD and ESAT6/CFP10. Regardless of HIV status and the severity of lung impairment, activation markers (CD38, HLA-DR and Ki67) on MTB-specific CD4+ T-cells declined after TB treatment initiation (p < 0.01), but the expression of the maturation marker CD27 did not change over the course of TB treatment. The MTB-specific T cell phenotype before, during and after treatment completion was similar between people living with and without HIV, as well as between subjects with severe and mild lung impairment. These data suggest that the assessment of activation and maturation markers on MTB-specific CD4+ T-cells can be useful for TB treatment monitoring, regardless of HIV status and the severity of lung disease.